Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Impact féministe sur l'art actuel: La Centrale à 40 ans = Feminist impact on contemporary art : La Centrale at 40 - Burisch, Nicole (La Centrale Galerie Powerhouse, 2015)
"Publication, célébrant les 40 ans d'engagement de la Centrale qui se voue au développement de l'histoire des pratiques artistiques féministes et soutient la visibilité d'artistes et d'initiatives moins ou peu représenté-es auprès des institutions culturelles établies"--Page 40.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; périodes historiques; québec; régions géographiques; sex1911; thématiques

Art et féminisme - Reckitt, Helena; Phelan, Peggy; Reckitt, Helena; Phelan, Peggy (Phaidon, 2011)
Depuis la fin des années 1960, le mouvement féministe a été à l'origine d'innovations, à la fois théoriques et pratiques, qui figurent parmi les plus intéressantes de l'art contemporain. Par ailleurs, certains succès politiques du mouvement féministe ont été obtenus grâce aux artistes, qui ont proposé de nouvelles manières d'envisager les domaines privé et public, l'objet de l'art et son sujet. En soulignant la différence des sexes, le courant féministe a aussi attiré l'attention sur le rôle de l'âge, de la classe sociale, de la race et de la sexualité dans la création artistique et dans sa réception. À la fois critiques et actrices du monde de l'art, les artistes féministes ont donné un nouvel élan à l'art considéré comme démarche à la fois politique et esthétique. Cet ouvrage, conçu par Helena Reckitt, présente les expériences, les idées et les démarches actuelles d'artistes majeures, et met en évidence le lien existant entre les différentes générations d'artistes. L'essai de Peggy Phelan, théoricienne de l'art et de la performance, jette un regard original sur les interprétations classiques de l'art des femmes et propose de nouvelles clés pour comprendre les rapports mouvants entre idées et idéaux du féminisme et pratiques artistiques.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques; théorie de l'art

WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Féminin pluriel et féminismes en arts visuels au Québec - Boileau, Julia (Esse, 2004)
Il y a plus de 20 ans, en tant qu’historienne de l’art, j’avais posé la question à savoir si l’apport des femmes en art contemporain allait changer quelque chose à la pratique artistique et comment, de même qu’à la pratique de la critique et de l’histoire de l’art1. Ce qui suit est une évocation des principaux questionnements que l’art des femmes et les féminismes en art ont amenés au sein de l’art contemporain. La pratique de l’art mais aussi les pratiques muséologiques ont-elles été affectées par l’arrivée en nombre des femmes sur la scène de l’art moderne et contemporain ? La question des femmes recèle-t-elle encore une pertinence dans le monde de l’art contemporain d’aujourd’hui ?
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; art contemporain; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques